EMERGENCY MEDICINE: A PRACTICE PRONE TO ERROR - Ali Awadh Alshammari, Faris Saad Alraddadi, Abdulmajeed Hameed Almhmadee, Mishal Humaidan Mohammed Al-Rashidi, Thari Dabis Awadh Alrashidi, Fahd Mansour Scholl Al-Rashidi, Zaher Khulaif Malreshidi, Fudhi Mufadhi Srour Alreshidi,,; Bandar Mohammed Saad Alhazmi, (Chelonian Research Foundation, 2022)
The last decade has witnessed a rapidly growing public and academic interest in medical error, an interest that has culminated in the emergence of the science of error prevention in health care. The impact of this new science will be felt in all areas of medicine but perhaps especially in emergency medicine (EM). The emergency department’s unique operating characteristics make it a natural laboratory for the study of error. These characteristics, combined with the complex and myriad activities of EM, predict vulnerability to a multitude of errors. Overcrowding and other resource limitations impair continuous quality improvement, and many errors result from high decision density, excessive cognitive load and flawed thinking in the decision-making process. A large proportion of these errors have serious outcomes but an even higher proportion are preventable. The historical practice of blaming individuals for errors needs to be replaced by root-cause analysis that identifies process and systemic weaknesses. Quantitative and qualitative methods are needed to detect, describe and classify error at all levels in the system, Research is needed into the processes that underlie EM error. Educational initiatives should be developed at all levels, for everyone from undergraduate trainees to practicing emergency physicians. Changes in societal attitudes will be an important component of the new culture of patient safety. Keywords: Emergency medicine, medical error, patient safety, error prevention, root cause analysis.